CHALLENGES FACED BY TEACHERS IN TEACHING ENGLISH TO YOUNG LEARNERS THROUGH SONGS - Cut Raudhatul Miski; Imro'atul Azizah; Najwa Amelia Arben; Nurhalimah; Siti Fadilah Sukma (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to explore the challenges faced by teachers when using songs as a medium for teaching English to young learners. A descriptive qualitative design was employed, involving one English teacher at SDN 192 Pekanbaru as the participant. Data were collected through an open-ended questionnaire and a semi-structured interview and were analyzed using thematic analysis. The findings revealed four major categories of challenges: teacher-related challenges, student-related challenges, classroom and school environment challenges, and song-specific challenges. The most prominent difficulties included limited teacher training, students' low motivation and limited English proficiency, inadequate learning facilities, and challenges related to pronunciation, vocabulary, and song tempo. From a Second Language Acquisition (SLA) perspective, fast musical tempo and connected speech make speech segmentation and listening comprehension particularly difficult for young learners. The study concludes that effective song-based instruction requires careful song selection, adequate institutional support, and appropriate scaffolding strategies to facilitate learners' language processing and comprehension.